Explor Neuroprot Ther 2022
DOI: 10.37349/ent.2022.00033
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in small fiber neuropathy

Abstract: Small fiber neuropathy (SFN) is a relatively common, but largely understudied neurological syndrome which has affected the lives of many globally. The common symptoms of SFN include pain, dysesthesia, and autonomic dysfunction, which are caused by damage to small nerve fibers. Due to its heterogeneous nature, SFN causes a multitude of symptoms which makes the disease and its subtypes difficult to diagnose. Furthermore, as the pathophysiology of SFN remains largely enigmatic, no cause is found in around 50% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…However, although experimental findings identified that NfL measurements discriminated between a length-dependent axonopathy and primary neuronopathy induced by TX and cisplatin in rats, respectively, we were unable to identify such differences in the degree of axonal loss among the different chemotherapy regimens or according to the pathogenetic mechanism of neurotoxicity. Besides the moderate sample size of our enrolled patients, other reasons may account for this lack of differences, mainly including that NCS can detect large fiber damage but are insensitive to changes in small diameter nerve fibers, which might also contribute to pNfL release [30], although conflicting results are emerging in the literature [31]. positively correlated with NfL levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, although experimental findings identified that NfL measurements discriminated between a length-dependent axonopathy and primary neuronopathy induced by TX and cisplatin in rats, respectively, we were unable to identify such differences in the degree of axonal loss among the different chemotherapy regimens or according to the pathogenetic mechanism of neurotoxicity. Besides the moderate sample size of our enrolled patients, other reasons may account for this lack of differences, mainly including that NCS can detect large fiber damage but are insensitive to changes in small diameter nerve fibers, which might also contribute to pNfL release [30], although conflicting results are emerging in the literature [31]. positively correlated with NfL levels [32].…”
Section: Discussionmentioning
confidence: 99%